1979
DOI: 10.1002/1097-0142(197911)44:5<1757::aid-cncr2820440533>3.0.co;2-8
|View full text |Cite
|
Sign up to set email alerts
|

Mucinous sweat gland adenocarcinoma of eyelid.A clinicopathologic study of 21 cases with histochemical and electron microscopic observations

Abstract: This is a clinicopathologic study of 21 cases of mucinous sweat gland adenocarcinoma involving the eyelid. The tumor occurred in middle-aged adults (median age 60 years) and has a predilection for males. In this series eight patients (40%) had one or more local recurrences, one of whom died with extensive local invasion of the face after multiple recurrences in a 15-year interval. Only one patient had metastasis to the submandibular lymph nodes, which was treated by radical neck dissection. Involvement of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
106
1
1

Year Published

1983
1983
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 158 publications
(110 citation statements)
references
References 14 publications
2
106
1
1
Order By: Relevance
“…Local recurrences are known to occur frequently in these tumours, but they rarely metastasize. Death following metastatic spread has been reported in three cases as per literature review [7,9]. No metastasis was detected in the present case.…”
Section: Introductionsupporting
confidence: 52%
See 1 more Smart Citation
“…Local recurrences are known to occur frequently in these tumours, but they rarely metastasize. Death following metastatic spread has been reported in three cases as per literature review [7,9]. No metastasis was detected in the present case.…”
Section: Introductionsupporting
confidence: 52%
“…Primary cutaneous mucinous carcinomas are slow-growing tumours with a local recurrence rate of 29.4% following excision and a low metastatic rate of 9.6% [6,7]. Majority of these tumours metastasize to regional lymph nodes.…”
Section: Introductionmentioning
confidence: 99%
“…4 Only 3 cases of death attributed to metastatic disease have been reported. [5][6][7] In a previous review of the literature that identified 206 published cases, 150 cases involved the head (eyelids, face, scalp, neck), while 7 involved the vulva. 8 There were no cases of PCMC involving the penis identified in our search of the PubMed database limited to publications in English.…”
Section: Discussionmentioning
confidence: 99%
“…It is a rare malignant tumor related to the eccrine sweat duct and is commonly located on the face, especially around the eyelids, and scalp 3,4 . It is usually solitary and grows asymptomatically over several months or even years 3 . Histopathology shows a circumscribed tumor with large amounts of mucin separated by fibrous septae and containing scattered floating islands of epithelial cells.…”
Section: Introductionmentioning
confidence: 99%